Cathepsin K analysis in a pycnodysostosis cohort: demographic, genotypic and phenotypic features - BEREKET, ABDULLAH; ARMAN, AHMET; ÇOKER GÜRKAN, AJDA; HALİLOĞLU, BELMA; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (BIOMED CENTRAL LTD, 2014)
Background: To characterize cathepsin K (CTSK) mutations in a group of patients with pycnodysostosis, who presented with either short stature or atypical fractures to pediatric endocrinology or dysmorphic features to pediatric genetics clinics. Methods: Seven exons and exon/intron boundaries of CTSK gene for the children and their families were amplified with PCR and sequenced. Sixteen patients from 14 families with pycnodysostosis, presenting with typical dysmorphic features, short stature, frequent fractures and osteosclerosis, were included in the study. Results: We identified five missense mutations (M1I, I249T, L7P, D80Y and D169N), one nonsense mutation (R312X) and one 301 bp insertion in intron 7, which is revealed as Alu sequence; among them, only L7P and I249 were described previously. The mutations were homozygous in all cases, and the families mostly originated from the region where consanguineous marriage rate is the highest. Patients with M1I mutation had fractures, at younger ages than the other pycnodysostosis cases in our cohort which were most probably related to the severity of mutation, since M1I initiates the translation, and mutation might lead to the complete absence of the protein. The typical finding of pycnodysostosis, acroosteolysis, could not be detected in two patients, although other patients carrying the same mutations had acroosteolysis. Additionally, none of the previously described hot spot mutations were seen in our cohort; indeed, L7P and R312X were the most frequently detected mutations. Conclusions: We described a large cohort of pycnodysostosis patients with genetic and phenotypic features, and, first Alu sequence insertion in pycnodysostosis.
Keywords: Cathepsin K; Pycnodysostosis; Fracture; Craniosynostosis; Arnold Chiari malformation; CONVERTING-ENZYME GENE; DELETION POLYMORPHISM; LA PYCNODYSOSTOSE; MOBILE ELEMENTS; MUTATIONS; CRANIOSYNOSTOSIS; ACTIVATION; DISEASE; GENOME